Local Government Expenditures on Care Services vs. Demographic Changes in Poland - Bobrowska, Agnieszka Monika (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
Local governments as the smallest units of territorial self‑government in Poland are responsible for providing care services. The growing number of the elderly can influence the expenditures level connected with ensuring proper care for them, and it may constitute a growing problem for local government, especially for districts with a lower level of socio‑economic development. In recent years, a quite high increase in benefits amount due to care services and specialist care services has been observed. Therefore, a question arises whether a significant dependence can be observed between the share of the elderly in the population and the degree of local governments’ financial burden due to providing care services. The aim of this paper is to indicate voivodeships where local governments bear the biggest burden of providing care services and to verify whether it is connected with their demographic situation. The data which were subject to the static analysis conducted came from public sources: the report of the Ministry of Family, Labour and Social Policy of the Republic of Poland and elaborations of the Central Statistic Office. The situation of particular voivodeships has been defined in the scope of society ageing and burdening local government with care services. Only in the case of half of voivodeships it has been proven that the level (low, medium or high) of burden of the said services corresponds to the same level of the number of the elderly in their population, which can confirm that the amount of care services is connected with a demographic situation of a given voivodeship.